PENGARUH DISIPLIN KERJA, MOTIVASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA PERCETAKAN SADHA JAYA DI DENPASAR - agus dwipayana, made; SUANA, WAYAN (E-Jurnal Manajemen, 2014)
Improving performance quality becomes a main goal of every developing company. The objective of this study is to investigate the influence of labor discipline, motivation and leadership style on employee performance either simultaneously or partially, and to determine the most influential variables of the employee’s performance at Sadha Jaya printing in Denpasar. The technique of collecting data applied in this study was observation, interviews and questionnaires. The respondents were 48 employees at Sadha Jaya printing in Denpasar. The data were tested by applying validity and reliability testing that aims to determine how far the variables studied have a degree of accuracy and consistency. Later, the data found were analyzed by using multiple linear regression analysis techniques, F test and T test. Keywords : work discipline, motivation, leadership styles and performance.